Spatiotemporal variability analysis of standardized precipitation indexed droughts using wavelet transform - Chong K.L.; Huang Y.F.; Koo C.H.; Najah Ahmed A.; El-Shafie A. (Elsevier B.V., 2023)
K-means clustering; Risk management; Stream flow; Testing; Wavelet transforms; Continuous wavelet transform; K-means++ clustering; Malaysia; Mann-Kendall test; Sarawak; Spatiotemporal variability; Spearman's rho; Standardized precipitation index; Drought; hydrometeorology; index method; precipitation (chemistry); precipitation (climatology); spatiotemporal analysis; wavelet analysis; East Malaysia; Malaysia; Sabah; Sarawak